ENDURANCE TRAINING MODEL FOR POLICE ACADEMY CANDIDATES - Kokom Supriyatnak; Iman Sulaiman; Widiastuti Widiastuti (Program Pascasarjana Universitas Negeri Jakarta, 2019)
This study aims to develop and implement endurance training models for political party candidates and obtain empirical data on the effectiveness and efficiency of the results of the development of endurance training models for political party candidates. Data is collected at PT. OCK Athletics Club in May 2019. Research and development in this exercise uses a qualitative and quantitative approach and uses the Research & Development (R&D) development model of Borg and Gall. Retrieval of data using a 12-minute running instrument (Guidelines for Administration of Physical Ability Tests and Anthropometric Examinations for Acceptance of Civil Servants in the National Police) with 60 subjects as PT students. OCK Athletic Club. Data collection techniques were processed using the onegroup pretest-posttest design, analyzed using t-test procedures and using the IBM Statistics application. The t-test results showed the final t-count of -10.999 on df showed 59 and Sig. (2-tailed) 0,000 <0.05 means that there was a significant difference in the endurance training model for Police Academy Candidates.